615 Targeted immune cell activation by systemic delivery of toll-like receptor 9 agonist antibody conjugates induce potent anti-tumor immunity. (10th December 2020) - Harrabi, Ons; Chen, Amy; Sangalang, Emma; Doyle, Laura; Fontaine, Danielle; Han, Bora; Bradshaw, Curt; Pons, Jaume; Sim, Janet; Kuo, Tracy; Wan, Hong
Abstract : Background: Toll-like receptor (TLR) pathways play a crucial role in mounting potent innate immune responses against invading pathogens, as well as the subsequent engagement of adaptive immunity. Innate immune activation via the TLR9 pathway has potential for treating cancer as demonstrated clinically with TLR9 agonists administered intra-tumorally in melanoma patients. 1 We developed a novel toll-like receptor agonist antibody conjugate (TRAAC) platform to systemically deliver a differentiated, targeted TLR9 agonist (T-CpG) for immune activation. The activation of TLR9 pathways can be directed systemically towards specific immune cell populations and tumor microenvironment via antibodies binding to various immune cell receptors. Using multiple TRAACs targeting either immune cells including plasmacytoid DCs (pDCs), myeloid and B lymphocytes, or tumor specific antigens, we evaluated immune modulatory phenotypes, therapeutic potentials, as well as safety and tolerability of this platform in pre-clinical settings. Methods: TRAACs were generated using site-specific conjugation. In vitro activity of immune- and tumor-targeted antibody-CpG conjugates was evaluated using human PBMCs. Anti-tumor efficacy and mechanistic assessment of B lymphocyte and myeloid cell-targeted antibody-CpG conjugates were conducted in syngeneic tumor models. Pharmacokinetic (PK), pharmacodynamic and exploratory toxicity evaluations were performed in non-human primates (NHP). Results: T-CpG is comprised of monomeric CpG-containing oligonucleotides optimized for potency and stability as an antibody conjugate. TRAACs targeting immune cells enable directed TLR9 activation leading to potent cytokine production and cellular activation that is superior to free CpG. This targeted immune activation also elicits a cascade of downstream modulation of non-targeted immune cells. When administrated systemically in multiple syngeneic models, murine TRAACs targeting either immune cells or tumor antigens exhibited potent, durable, and dose-dependent anti-tumor activity as a single agent and in combination with T-cell checkpoint inhibitors (CPIs). A single peripheral dose of either B lymphocyte or myeloid targeted-CpG evoked both innate and adaptive immune responses within the tumor microenvironment as demonstrated by NanoString analysis. The observed immunomodulatory phenotypes are consistent with those elicited by direct intra-tumoral CpG delivery. Following repeated intravenous doses in NHP, TRAACs demonstrated targeted receptor occupancy, antibody-like PK, and favorable tolerability profile. Conclusions: Pre-clinical evaluation of a novel platform comprised of antibodies conjugated to a differentiated TLR9 agonist demonstrated targeted immune activation, potent anti-tumor activity as single agent and in combination with CPIs and favorable tolerability profiles in NHPs. Such antibody-CpG conjugates have the potential for clinical development as systemically delivered therapeutics providing powerful innate and adaptive anti-tumor immunity across multiple tumor types. Reference: Hamid O, Ismail R, Puzanov I. Intratumoral Immunotherapy—Update 2019. The Oncol 2019; 25 :343–359.